Surto de salmonella enteritidis/enteridis em granja produtora de frango caipira na região sul do maranhão - Pigatto, C. P. (2009)
The aim of this trial was to detect the agent that causes high mortality of chickens in a farm in the south of Maranhão, Brazil, as well as determining the infection source. Necropsy of the chickens was done and carried through bacteriological analyses of liver, intracardiac blood and chicken food. The samples taken from the heart blood, liver and initial chicken feed had presented characteristic colonies of Salmonella. These colonies had been submitted to the biochemical and serologic tests for evidence of the patogenicity. Salmonelosis is considered an important disease in the poultry keeping and can cause serious ambient and economic losses, beyond the problem of public health. This paper stands out the importance of a good sanitary handling and programs of control and prevention of illnesses in the animal breeding.